Thaipusam in Malaysia: An analysis of a Hindu festival (A study of Batu Caves, Selangor) / Neelavani S. Thanabalan - Neelavani , S. Thanabalan (1988)
In Malaysian context Thaipusam festival has become the major and most popular festival among the Hindu festivals. A study on Thaipusam festival will help to explain the religious belief of Hindus in Malaysia. Chapter I: contains information on introduction, aims, and scope of this &tudy. Various method that were used and the problems that arise during the research are also touched in this chapter. Chapter II: a brief definition on Hinduism are given. A short history of Hinduism development in Malaysia are also emphasized. Chapter III: deals s with discussion regarding the tradition of Thaipusam. The meaning of Thaipusam, the myth behind the featival, various places in the world that celebrates Thaipusam, and the main location of this festival in Malaysia are given. This chapter also deals with t he aims of taking kavathi . The various form of kavathi are also highlighted. Chapter IV : explain the preparation process and rituals a kavati-carrier undergoes to fulfill his or her vow. Chapter V : describe the organisation process of Thaipusam festival in Kuala Lumpur. A few interesting sceneries that can be seen at Batu Caves site will be highlighted. Chapter VI : will give an analysis of changes that had occur in Thaipusam festival in these recent years. Does the changes have positive or negative consequences to Hindu doctrine. It will also describe the politics involved in this festival. Finally, some suggestive remarks are given on how to overcome the short coming of this festival. This is to ensure the purity of Taipusam festival in the midst of rapid developing Hindu society in Malaysia.